2022
DOI: 10.1073/pnas.2116588119
|View full text |Cite
|
Sign up to set email alerts
|

Mass cytometry reveals single-cell kinetics of cytotoxic lymphocyte evolution in CMV-infected renal transplant patients

Abstract: Cytomegalovirus (CMV) infection is associated with graft rejection in renal transplantation. Memory-like natural killer (NK) cells expressing NKG2C and lacking FcεRIγ are established during CMV infection. Additionally, CD8+ T cells expressing NKG2C have been observed in some CMV-seropositive patients. However, in vivo kinetics detailing the development and differentiation of these lymphocyte subsets during CMV infection remain limited. Here, we interrogated the in vivo kinetics of lymphocytes in CMV-infected r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 46 publications
3
13
0
Order By: Relevance
“…The prevalence of chronic CMV infection in most countries increases with age ( Fowler et al, 2022 ) and is best known for the inflationary effect it has on the T-cell compartment, particularly in driving clonality in CD8 + T-cells, resulting in an increase in subsets exhibiting an exhausted, senescent-like phenotype, while potentially exacerbating a reduction of the overall pool of naïve subsets ( Nikolich-Žugich, 2018 ). Evidence from experimental models ( Fehniger et al, 2007 ) and longitudinal studies ( van Leeuwen et al, 2004 ; Ishiyama et al, 2022 ; Vaaben et al, 2022 ) indicates that CMV is an important determinant of the abundance of GZB+ NK-cell and CD8 + and γδ T-cells, in line with our own findings. However, ours appears to be the first documentation of the cell-specific patterns of GZK expression in older adults, although a previous study showed that serum levels of GZK increase with CMV infection ( Bade et al, 2005 ).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The prevalence of chronic CMV infection in most countries increases with age ( Fowler et al, 2022 ) and is best known for the inflationary effect it has on the T-cell compartment, particularly in driving clonality in CD8 + T-cells, resulting in an increase in subsets exhibiting an exhausted, senescent-like phenotype, while potentially exacerbating a reduction of the overall pool of naïve subsets ( Nikolich-Žugich, 2018 ). Evidence from experimental models ( Fehniger et al, 2007 ) and longitudinal studies ( van Leeuwen et al, 2004 ; Ishiyama et al, 2022 ; Vaaben et al, 2022 ) indicates that CMV is an important determinant of the abundance of GZB+ NK-cell and CD8 + and γδ T-cells, in line with our own findings. However, ours appears to be the first documentation of the cell-specific patterns of GZK expression in older adults, although a previous study showed that serum levels of GZK increase with CMV infection ( Bade et al, 2005 ).…”
Section: Discussionsupporting
confidence: 87%
“…Although the sample of young adults was relatively small, the MFI of GZB for CD4 + and CD8 + T-cells was also significantly higher in CMV-positive participants (standardized β [95% CI]: CD4 = 1.27 [.002, 2.534], CD8 = 1.38 [.42, 2.33]). Finally, since CMV infection and reactivation have been shown to drive perforin expression in NK- and CD8 + T-cells, respectively ( Pietersma et al, 2010 ; Ishiyama et al, 2022 ), and perforin is a critical mediator of the cytolytic response of those cells ( McElhaney et al, 2020 ), we also investigated whether the aforementioned associations between CMV and GZB/GZK+ cell frequency were dependent on perforin expression. There was a tendency for the associations between CMV seropositivity and GZB+ CD8 + and Vδ1+ cells or GZK+ CD4 + and CD8 + cells to be stronger for the perforin positive vs. negative subsets ( Supplementary Figure S1A ), which was similarly present when considering the ratio of perforin positive to negative cells within each cell population ( Supplementary Figure S1B ).…”
Section: Resultsmentioning
confidence: 99%
“…The nature of HSCT transplant conditioning and donor choice is likely to impact substantially on the profile of NK reconstitution and similar findings have been seen after umbilical donor transplantion ( 22 )although an increase in NK number was not seen in the setting of haploidential transplantation ( 25 , 26 ). In the renal transplant setting a recent study has revealed a similar finding of increased number and frequency of NK cells after HCMV reactivation ( 27 ).…”
Section: Discussionmentioning
confidence: 68%
“…Interestingly, the PI3K/AKT signaling pathway was remarkably enriched ( Figure 7 D). The PI3K/AKT pathway has been demonstrated to be involved in the EMT of several types of human cancer [ 33 , 34 , 35 , 36 ]. To explore whether PI3K/AKT signaling was involved in AGT-mediated EMT, we examined the effect of AGT on the activation of PI3K/AKT.…”
Section: Resultsmentioning
confidence: 99%